Ibn al-Haytham an Arab Scholar Who Laid the Foundation of Physiological Optics and Spectacles Policy - Puyan, Nasir (Current Research in Language, Literature and Education Vol. 2, 2021)
Ibn al-Haytham, Muslim mathematician and physicist with an unknown actual life who laid the foundation of physiological optics and came within an ace of discovery of the use of eyeglasses. He wrote a lot about algebra, geometry, and astronomy. Eyeglasses were used as a vision aid in Europe as early as the 13th century, but Alhazen's book "Kitab al – Manazir" (Book of Optics) included theories on refraction, reflection, and the study of lenses, and provided the first account of vision. During the Middle Ages, it wielded considerable power. He explained in it that twilight was caused by the refraction of the sun's rays in the earth's atmosphere. Robert Grosseteste, a clergyman from Sussex, England, wrote the first Latin translation of Alhazen's mathematical works in 1210. In 1572, his astrological treatise was published in Latin at Basle. Alhazen, a Basra native, died in Cairo at the age of 73.